TADF‐Type Organic Afterglow - Wang, Xuepu; Sun, Yan; Wang, Guangming; Li, Jiuyang; Li, Xun; Zhang, Kaka (Angewandte Chemie International Edition, 2021)
We report a highly efficient dopant‐matrix afterglow system enabled by TADF mechanism to realize afterglow quantum yields of 60–70 %, which features a moderate rate constant for reverse intersystem crossing (kRISC) to simultaneously improve afterglow quantum yields and maintain afterglow emission lifetime. Difluoroboron β‐diketonate (BF2bdk) compounds are designed with multiple electron‐donating groups to possess moderate kRISC values and are selected as luminescent dopants. The matrices with carbonyl functional groups such as phenyl benzoate (PhB) have been found to interact with and perturb BF2bdk excited states by dipole–dipole interactions and thus enhance the intersystem crossing of BF2bdk excited states. Through dopant‐matrix collaboration, the efficient TADF‐type afterglow materials have been achieved to exhibit excellent processability into desired shapes and large‐area films by melt casting, as well as aqueous afterglow dispersions for potential bioimaging applications. Due to the spin‐forbidden nature, it remains challenging to achieve room‐temperature organic phosphorescence and afterglow materials with high quantum yields. We report a highly efficient dopant‐matrix afterglow system enabled by TADF mechanism to realize afterglow quantum yields of 60–70 %, which features a moderate rate constant for reverse intersystem crossing to simultaneously improve afterglow quantum yields and maintain afterglow emission lifetime.